Hydrogen sulfide activatable metal-organic frameworks for Fluorescence Imaging-Guided Photodynamic Therapy of colorectal cancer - Li, Honghui; Huang, Mao; Wei, Zixuan; He, Jiawen; Ma, Yunong; Lu, Cuixia; Jin, Albert; Wang, Zhixiong; Wen, Liewei (Frontiers in Bioengineering and Biotechnology, 2022)
Photodynamic therapy (PDT) is a promising alternative and palliative therapeutic strategy for colorectal cancer (CRC). A novel photosensitizer with higher selectivity for CRC and fewer side effects is vital for clinical application. Given that the overexpression of hydrogen sulfide (H2S) in CRC, it is expected to provide a selective stimulus for activatable photosensitizers that in respond to the specific microenvironment. Herein, we report a novel development of metal-organic frameworks (MOFs) composed of meso-Tetra(4-carboxyphenyl) porphine (TCPP) and ferric ion (Fe3+) through a facile one-pot process. Experiments both in vitro and in vivo reveal that the MOF is capable of depredating in response to the high content of H2S in tumor microenvironment of CRC. Accompanying with the degradation and release of TCPP, the fluorescence and photosensitivity effect is switched from “off” to “on”, enabling the MOF to serve as a H2S activatable nano-photosensitizer for real-time fluorescence imaging-guided and targeted PDT of CRC.